Hubungan Antara Derajat Histopatologik Sarkoma dengan Respon Radioterapi - Soesilowati, Eny; Afiati; Yulianti, Herry; Aminah, Hermin; Hernowo, PhD, SpPA(K), Bethy Surjawathy (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundSarcomas are rare, aggressive tumors originating from mesenchymal tissue. Radiotherapy is currently accepted as thestandard adjuvant to the treatment of high-grade sarcomas, whereas low-grade sarcomas are controversial, but the response ofradiotherapy to sarcomas is up to 50%. The aim of this study was to determine the association between the histopathologicalgrade of sarcoma and the radiotherapeutical response.MethodsThe research design was a cross-sectional study, with retrospective analysis. The sample consisted of 80 paraffin block tissuesfrom biopsy and surgery specimens of sarcoma from January 2013 to December 2019 at Hasan Sadikin Hospital in Bandung,consisting of 45 radiosensitive samples and 35 radioresistant samples. All samples were assessed for histopathological gradeaccording to the FNCLCC. Statistical analysis used the Chi-Square test with a significant value of p <0.05. Data were processedusing SPSS version 24.0 for windows.ResultsIn the radiosensitive group, 15 (33.3%) samples were low grade sarcomas and 30 (66.7%) samples were high grade sarcoma.There was no statistically significant association between histopathological grade and radiotherapeutical response in sarcomasp> 0.05 (p = 0.304).ConclusionIn this study, the radiotherapeutical response was not associated to the histopathological grade of sarcoma. This is because ofthe sensitivity of radiotherapy is influenced by other factors including molecular characteristics.